A Process Model for Deployment Planning of Ground-based Air Defense System Against Asymmetric Homeland Threat - Cypert, Ronald L. (2009)
see The Joint Air Defense Operations - Homeland (JADO-H) Joint Test (JT) was chartered on August 15, 2007, in support of North American Air Defense Command (NORAD) / U.S. Northern Command (NORTHCOM) mission to protect the homeland against asymmetric air and cruise missile attacks. The JADO-H test team was given the specific focus of developing planning tactics, techniques, and procedures supporting the Deployable - Homeland Air and Cruise Missile Defense (D-HACMD) concept of operations (CONOPS) completed by NORAD in 2005. Since completion of the CONOPS, an actual deployment of this ground-based Army missile point-defense system in the homeland has occurred only twice-.on both occasions there were several months of planning lead time required for successful coordination. As can be imagined the ability to deploy this system in a crisis situation is critical. Because planning for this mission area encompasses so many Department of Defense organizations and echelons of command, i.e. NORAD/NORTHCOM, U.S. Army North (ARNORTH), U.S. Air Force North (AFNORTH), CONUS NORAD Region (CONR), National Guard Bureau, U.S. Joint Forces Command (JFCOM), Air Combat Command (ACC), Forces Command (FORSCOM), Army air defense units, Air Force communication units, along with coordination at the state and federal agency level, a dynamic process modeling capability was chosen to chart the myriad interactions among these disparate organizations. Live-Virtual Constructive Conference, 12-15 Jan 2009, El Paso, TX. The original document contains color images.